Implementing Business Judgment Rules in Corporate Decision-Making: A Focus on the Tourism Industry - Johan, Suwinto (LPPM Universitas Ekasakti Padang, 2024)
The Board of Directors assumes responsibility for managing a Limited Liability Company, making decisions amidst uncertain circumstances that may lead to company losses. Directors must adherence to the principles of the business judgment rule and act without conflict of interest and with utmost good faith towards the company's best interests. This study explores the application of business judgment rules by directors in corporate governance, employing normative juridical methods. Directors' accountability for company losses under these rules were examined based on the primary, secondary, and other relevant data sources. The research concludes that directors can effectively apply business judgment rules when they operate with integrity and prioritize the company's well-being, emphasizing the importance of maintaining good corporate governance standards.